Global South Research Collaboration: A Comparative Perspective - Gueye, Abdoulaye; Choi, Edward; Guzmán-Valenzuela, Carolina; Gregorutti, Gustavo (International Journal of African Higher Education, 2022)
Research collaboration has become a major research topic in the social sciences. While this literature has mainly focused on collaborative dynamics in the Global North, more recent studies have examined these dynamics within the Global South. This article expands the scope of analysis by comparing the level of co-publications by Global South-based scholars with Global South-based colleagues and that between academics at Global South institutions and researchers in Global North universities. It shows that academic partnerships within the Global South are less common than instances of collaboration between the Global South and Global North. The relatively weak Global South collaborative dynamics are at odds with most Global South leaders’ encouragement of partnerships between scholars within the South. The article also demonstrates that collaboration seems to be largely informed by linguistic commonality and historical (colonial) relations of dependency. Contrary to expectations that US-based academics would be the primary partners for Global South academics due to US hegemony, the latter are more likely to collaborate with colleagues in European countries, more specifically countries that colonised their countries.